ANTIDIABETIC PROPERTIES OF TRADITIONAL INDONESIAN MEDICINAL PLANTS: A SCOPING REVIEW OF PRECLINICAL AND CLINICAL EVIDENCE ABSTRACT - Wildana, Fahmi; Efendi, Melani Adelia; Trisna, Azhari; Mahmudi, Fikri Ali; Sitorus, Ulina Debora Junita Sitorus Debora Junita (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2026)
Introduction: Diabetes mellitus (DM) poses a major global health burden, particularly in low- and middle-income countries where access to care and medication costs remain challenging. Indonesia, a biodiversity hotspot with extensive ethnomedicinal heritage, offers numerous traditional plants with potential antidiabetic properties. This study aimed to systematically map preclinical and clinical evidence on the antidiabetic activity of traditional Indonesian medicinal plants.Method: A scoping review was conducted using PubMed, Scopus, and Google Scholar databases (2015–2025). Studies were included if they evaluated Indonesian medicinal plants for antidiabetic effects in preclinical (in vitro/in vivo) or clinical settings. Screening followed the PRISMA-ScR framework, and methodological quality was assessed using the Joanna Briggs Institute (JBI) appraisal tools.Results: Twenty primary studies met the inclusion criteria (17 preclinical, 3 clinical). Preclinical studies consistently demonstrated reductions in blood glucose, improved insulin secretion and sensitivity, β-cell protection, and antioxidant effects. Notable species included Andrographis paniculata, Muntingia calabura, Artocarpus heterophyllus, Ocimum basilicum, and Gynura procumbens. Clinical trials involving cinnamon, ginger, and Momordica charantia showed moderate glycemic improvements (fasting blood glucose −6.3%, HbA1c −0.5%) but were limited by small sample sizes, heterogeneous extract preparations, and short durations.Conclusion: Indonesian traditional medicinal plants exhibit promising antidiabetic potential through multiple mechanisms and may serve as safe adjuvant therapies for diabetes management. However, clinical validation remains insufficient. Future research should emphasize large-scale randomized controlled trials with standardized extracts, extended intervention durations, and comprehensive outcome measures to support evidence-based integration into clinical practice.